2012
DOI: 10.1007/s00360-012-0668-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ocean acidification on respiratory gas exchange and acid–base balance in a marine teleost, Opsanus beta

Abstract: The oceanic carbonate system is changing rapidly due to rising atmospheric CO(2), with current levels expected to rise to between 750 and 1,000 μatm by 2100, and over 1,900 μatm by year 2300. The effects of elevated CO(2) on marine calcifying organisms have been extensively studied; however, effects of imminent CO(2) levels on teleost acid-base and respiratory physiology have yet to be examined. Examination of these physiological processes, using a paired experimental design, showed that 24 h exposure to 1,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 68 publications
9
129
1
Order By: Relevance
“…A few studies have reported downregulation of VHA mRNA in gills from fish exposed to OA (e.g. Esbaugh et al, 2012;Tseng et al, 2013), which, as pointed out in a recent review (Heuer and Grosell, 2014), was most likely due to downregulation of branchial HCO 3 − secretion to seawater and H + reabsorption into the blood.…”
Section: A/b Regulationmentioning
confidence: 91%
“…A few studies have reported downregulation of VHA mRNA in gills from fish exposed to OA (e.g. Esbaugh et al, 2012;Tseng et al, 2013), which, as pointed out in a recent review (Heuer and Grosell, 2014), was most likely due to downregulation of branchial HCO 3 − secretion to seawater and H + reabsorption into the blood.…”
Section: A/b Regulationmentioning
confidence: 91%
“…At present, there are few reports on the influence or not of ocean acidification on the metabolic performance of tropical fish species. In this regard, it will be important to explore whether or not tropical fish have the same challenges that temperate fish have when it comes to respiratory gas transport and acid-base balance (Esbaugh et al, 2012;Pörtner et al, 2014). Physiological impacts combined with ecological impacts and habitat degradation, are likely to generate "surprises" for complex ecosystems such as those associated with both cold and warm water coral reefs.…”
Section: Biological Responses To a Rapidly Warming And Acidifying Oceanmentioning
confidence: 99%
“…P CO2 between 600 and 2000 µatm). The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%